2018
DOI: 10.2478/raon-2018-0005
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases polymorphisms as baseline risk predictors in malignant pleural mesothelioma

Abstract: BackgroundMalignant mesothelioma (MM) is a rare disease, linked to asbestos exposure in more than 80% of the cases. Matrix metalloproteinases (MMPs) have been identified as modulators of the tumour microenvironment and carcinogenesis. Polymorphisms of selected MMPs have been studied as potential biomarkers of time to progression (TTP) and overall survival (OS) in MM. The aim of our study was to investigate selected MMP polymorphisms as baseline risk predictors in MM development in combination with other well k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Serum samples were prepared immediately after blood sampling, aliquoted, and stored at −20°C until MMP9 levels were measured. The remaining blood peripheral lymphocytes were used for DNA isolation, and all the patients have been genotyped for common MMP2 , MMP9 , and MMP14 polymorphisms [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum samples were prepared immediately after blood sampling, aliquoted, and stored at −20°C until MMP9 levels were measured. The remaining blood peripheral lymphocytes were used for DNA isolation, and all the patients have been genotyped for common MMP2 , MMP9 , and MMP14 polymorphisms [17].…”
Section: Methodsmentioning
confidence: 99%
“…However, MMP9 and MMP2 as potential biomarkers in MM did not reach diagnostic value as potential standalone biomarkers and more studies are needed to evaluate the role of soluble MMP9 in MM. We have shown that MMP9 rs2250889 CG genotype carriers had significantly shorter overall survival (OS) and time to progression (TTP), while MMP9 rs20544 CT allele carriers had longer OS [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Three SNPs in MMP2 (rs1053605, rs243849, and rs14070) were selected to identify MMP2 candidate SNP variants based on NCBI database ( https://www.ncbi.nlm.nih.gov/snp ), minor allele frequency (MAF) >5%, and SNP was better assessed in previous studies ( 9 , 18 20 ). After the extraction and purification of the above-mentioned sample DNA, primers for candidate SNPs (rs1053605, rs243849 and rs14070) were designed based on the gene sequence of MMP2 using Primer5.0 primer design software ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a study that included 236 mesothelioma patients and 161 healthy blood donors, carriers of at least one polymorphic MMP2 rs243865 allele had significantly lower risk for mesothelioma. This association was even more pronounced in patients exposed to asbestos, indicating that this SNP could be used as a potential baseline risk predictor in mesothelioma [ 25 ].…”
Section: Mmps Genetic Variability In Mesotheliomamentioning
confidence: 99%